The Process of Mental Recovery in Adolescents - Siddiqov Sardorbek Zafarjon o’g’li (Academia One, 2023)
The abstract of the topic of the process of mental recovery in adolescents is likely to focus on the difficulties that adolescents face in getting rid of mental health problems, such as depression, anxiety and trauma can. In addition, it can highlight the role of technology and social media in shaping adolescents ' mental health and recovery expectations.
Keywords: mental recovery; adolescence; health problems